Asas Pacta Sunt Servanda dalam Pembagian Harta Pusaka Berdasarkan Ganggam Bauntuak Iduik Bapadok dalam Masyarakat Adat Minangkabau (Studi Kasus Putusan Mahkamah Agung Republik Indonesia Nomor 2651 K/Pdt/2022) - Anisa Salsabila (LPPM Universitas Ekasakti Padang, 2023)
Modern human life is closelyarelated to legal acts, transactions and agreements. This article reviews the concept of agreementaaccordingy top Articlep 1313 rofpthep Civilp Code, emphasizing that the term